Situational analysis of the communication flow in audiovisual media - Carlos Aguilar; Lydia Sánchez; Manuel Campos (tripleC: Communication, Capitalism & Critique)
This paper presents a mathematical framework for the study of the information contained in audiovisual contents based on the development by Keith Devlin of Situation Theory. In order to obtain this framework, we present accounts of the processes carried out by agents from the reception of audiovisual contents to the extraction of information, in accordance with the definition by Israel and Perry. We finally justify why these accounts concerning the extraction of information from audiovisual content can be included as part of a mathematical formulation of Situation Theory